Socio-demographic, economic and health profile of adults with sickle-cell disease - Júlia Lamese Amaral; Nívea Aparecida Almeida; Paula Silveira Santos; Patrícia Peres de Oliveira; Fernanda Moura Lanza (Rev Rene)
Objective: to describe socio-demographic and economic characteristics, lifestyle, clinical manifestations, use of medicationsand monitoring of adults with sickle-cell disease. Methods: a descriptive study with quantitative approach, made with 20adults, registered in a Hematology and Hemotherapy Center, using, for data collection, interviews in the participant’s homeand medical records. In order to have the database, the EpiDatae analysis software through statistical program was used.Results: most of the population consisted of women, married, with complete high school, which used exclusively the UnifiedHealth System. The average age was 30.6 years, and 90.0% (95% CI 68.3-98.8) were black. All of them reported painful crisesand fatigue. They used folic acid daily 35.0% (95% CI 15.4-59.2). Conclusion: the implications of sickle-cell disease could bemitigated through primary, secondary and tertiary health care, according to the needs of those adults.